On the green factorization method and supersymmetry - Tan, M. Y.; M. S., Nurisya; H., Zainuddin (IOP Publishing, 2022)
The factorization method in operator language formalism and supersymmetric quantum mechanics are vastly studied in literature. The well-known factorization method goes to the early work by Infeld and Hull in 1951. However, a different formalism of factorization method introduced by Green in 1965 is less being considered by the researchers. We show that the Green factorization method, also known as the deductive method, has a connection with supersymmetric quantum mechanics. Some anharmonic quantum systems are discussed by obtaining their analytical expressions for the complete spectrum of bound states and superpotential through the Green factorization method.